2023
DOI: 10.1007/s00134-023-07154-0
|View full text |Cite
|
Sign up to set email alerts
|

Towards model-informed precision dosing of piperacillin: multicenter systematic external evaluation of pharmacokinetic models in critically ill adults with a focus on Bayesian forecasting

Abstract: Purpose Inadequate piperacillin (PIP) exposure in intensive care unit (ICU) patients threatens therapeutic success. Model-informed precision dosing (MIPD) might be promising to individualize dosing; however, the transferability of published models to external populations is uncertain. This study aimed to externally evaluate the available PIP population pharmacokinetic (PopPK) models. Methods A multicenter dataset of 561 ICU patients (11 centers/3654 concentrations) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Finally, some of the models used in the MIPD software may have been unable to accurately predict target exposures as the models used total antibiotic concentrations while the investigators used unbound concentrations for TDM measurements [ 28 ]. Commentators have highlighted the absence of external validation of some of the models used by the software [ 29 ], while a recent multicentre evaluation of 24 popPK piperacillin models illustrated substantial inter-model variability leading to highly variable predictive performance [ 30 ]. However, meta-analyses of individualised antimicrobial dose optimisation confirm the achievement of higher rates of target exposures and have suggested reductions in treatment failure and adverse outcomes, such as nephrotoxicity [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, some of the models used in the MIPD software may have been unable to accurately predict target exposures as the models used total antibiotic concentrations while the investigators used unbound concentrations for TDM measurements [ 28 ]. Commentators have highlighted the absence of external validation of some of the models used by the software [ 29 ], while a recent multicentre evaluation of 24 popPK piperacillin models illustrated substantial inter-model variability leading to highly variable predictive performance [ 30 ]. However, meta-analyses of individualised antimicrobial dose optimisation confirm the achievement of higher rates of target exposures and have suggested reductions in treatment failure and adverse outcomes, such as nephrotoxicity [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several piperacillin population pharmacokinetic models are available in the literature, predominantly with the consideration of single- or, more often, two-compartment models including creatinine clearance as a covariate [ 22 , 23 , 24 ]. Nevertheless, it has recently become apparent that the suitability of these models for making estimates of individual pharmacokinetic properties can be highly variable.…”
Section: Discussionmentioning
confidence: 99%
“…A multicenter study revealed only three models which provided acceptable estimates and absolute prediction errors. Interestingly, the authors of this study concluded that the accuracy of estimates was gender-dependent [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, some of the models used in the MIPD software may have been unable to accurately predict target exposures as the models used total antibiotic concentrations while the investigators used unbound concentrations for TDM measurements [25]. Commentators have highlighted the absence of external validation of some of the models used by the software [26], while a recent multicenter evaluation of 24 popPK piperacillin models illustrated substantial inter-model variability leading to highly variable predictive performance [27]. Meta-analyses of individualised antimicrobial dose optimisation con rm the achievement of higher rates of target exposures and have suggested reductions in treatment failure and adverse outcomes such as nephrotoxicity [28,29].…”
Section: Discussionmentioning
confidence: 99%